Upaya Peningkatan Kemampuan Koneksi dan Kemampuan Berpikir Kritis Siswa melalui Pendekatan Differentiated Instruction: Penelitian Tindakan Kelas pada Materi Komplemen Himpunan di Siswa Kelas VII E SMP Negeri 3 Majalengka - Suhana, Nana (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
The purpose of this study is to improve critical thinking skills and mathematical connections in learning mathematics. This research is an action research with collaborative implementation between observers and researchers as actors of action. The research step is a reflection of action with the pattern of "Recycled Assessment Process (Cycle)". This step is carried out repeatedly consisting of Planning-Action-Observation-Reflection. The research was carried out from July 2022 until the end of semester 1 in December 2022. The subjects in this study were class VII E students of SMP Negeri 3 Majalengka in the academic year 2021-2022. The number of students is 32 people consisting of 16 male students and 16 female students. Based on the results of data analysis and discussion of the effect of learning using the implementation of the differentiated instruction approach on improving connection skills and critical thinking skills of Class VII E students of SMP Negeri 3 Majalengka, Majalengka Regency, the following conclusions are put forward: Improving connection skills and critical thinking skills of students who receive learning by using the implementation of the differentiated instruction approach is significantly better